IMPLEMENTASI KEBIJAKAN SAK UWONG SAK UWIT (SUSU) DI KABUPATEN KENDAL - Ajeng Yuanitasari; Puji Astuti; Supratiwi . (Journal of Politic and Government Studies, 2014)
ABSTRACTGlobal warming it is currently being one the problems faced by the worldthat happened in one of them is due to activity felling trees.Indonesia as one of thecountries undergoing global warming. This happened because an extensive forestin indonesia from year to year is shrink. Management environment now this intothe affairs and responsibility of the government.Regional autonomy possibilitieslot for management of the living better, thus local can make policyenvironmentally sound. Regency Kendal is one who offers policy isenvironmentally sound policy Sak Uwong Sak Uwit (SUSU ).T he policy obligingcouples prospective brides and post-delivered-mothers for planting trees, forprospective brides prior to ijab qobul compulsory plant two trees.This research aims to find out how the implementation of policies of SakUwong Sak Uwit (SUSU) in the Regency of Kendal as well as any barriersexperienced by Kendal Regency Government. The methods used in this researchusing qualitative methods. The qualitative method is a method in which toconduct research using the techniques of observation or interviews.The results of research that has been done by researchers is in theimplementation of policies of Sak Uwong Sak Uwit (SUSU) in the Regency ofKendal is still in the stage of dissemination policy conducted by the Governmentthrough the coordination meeting of the Kendal District or Department meetings,while the implementation of Sak Uwong Sak Uwit (SUSU) in the village has yetto run its full potential because of a lack of commitment to the village chief. In theimplementation of policies of Sak Uwong Sak Uwit (SUSU) in the Regency ofKendal there are also constraints encountered, namely: 1. the lack of socializationto society, 2. the lack of financial resources and facilities, 3. lack of commitmentand a good kerjasaman which is owned by the Government of Kendal and 4. Yetthe existence of technical instructions that govern the implementation of thepolicy of Sak Uwong Sak Uwit (SUSU).Keywords: implemetasi, public policy, environmental management